THE FINE STRUCTURE OF THE ELECTRIC ORGAN OF TORPEDO MARMORATA - Sheridan, Michael N. (The Rockefeller University Press, 1965)

(untitled)
The fine structure of the electric organ of the fish Torpedo marmorata has been examined after osmium tetroxide or potassium permanganate fixation, acetone dehydration, and Araldite embedment. This organ consists of stacks of electroplaques which possess a dorsal noninnervated and a ventral richly innervated surface. Both surfaces are covered with a thin basement membrane. A tubular membranous network whose lumen is continuous with the extracellular space occupies the dorsal third of the electroplaque. Nerve endings, separated from the ventral surface of the electroplaque by a thin basement membrane, contain synaptic vesicles (diameter 300 to 1200 A), mitochondria, and electron-opaque granules (diameter 300 A). Projections from the nerve endings occupy the lumina of the finger-like invaginations of the ventral surface. The cytoplasm of the electroplaques contains the usual organelles. A "cellular cuff" surrounds most of the nerve fibers in the intercellular space, and is separated from the nerve fibre and its Schwann cell by a space containing connective tissue fibrils. The connective tissue fibrils and fibroblasts in the intercellular space are primarily associated with the dorsal surface of the electroplaque.